1976
DOI: 10.1021/jo00870a019
|View full text |Cite
|
Sign up to set email alerts
|

The stereodependent effect of oxygen on the chemical shifts and vicinal coupling constants of tetrahydropyran

Abstract: The analysis of the ' H NMR spectra of two selectively deuterated derivatives of tetrahydropyran at -115 O C has provided accurate values for proton chemical shifts and vicinal coupling constants about the C(2)-C(3) bond. A comparison with the corresponding parameters of cyclohexane allows a precise definition of the stereodependent effect of oxygen (3J2a3a, 3J2e3e, 3J2a3e are reduced while 3J2e3a is increased) in this fundamental molecule. An explanation of the trends observed is given and the conformational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Lambert et al 12 examined deuterated analogues and reported the ∆G ‡ and coupling data, but no chemical shift data. Late work by Lambert et al 13 and a detailed study by Canuel and St.-Jacques, 14 again on deuterated THP, excluded the H3 and H4 chemical shifts. These analyses were in different solvents, CD 3 OD-CHClF 2 and CS 2 , with the former only giving ∆(δeq Ϫ δax) values.…”
Section: Introductionmentioning
confidence: 99%
“…Lambert et al 12 examined deuterated analogues and reported the ∆G ‡ and coupling data, but no chemical shift data. Late work by Lambert et al 13 and a detailed study by Canuel and St.-Jacques, 14 again on deuterated THP, excluded the H3 and H4 chemical shifts. These analyses were in different solvents, CD 3 OD-CHClF 2 and CS 2 , with the former only giving ∆(δeq Ϫ δax) values.…”
Section: Introductionmentioning
confidence: 99%
“…Br Br X 8 X:Bf, R:fV:Y:H 14 Y:OMe, R':Ac, R: X :H 9 Y:Br, R:R':X:H 15 R:OMe, R':X:Y:H 10 X:Y:Br, R:R':H 16 R:OMe,R':Ac, X:Y:H 1 3 Y:OM•, R:R':X:H dominant biindoles, together with a small amount of (+)-2,5,5,-tribromo-7,-methoxy-3,4'-bi-l//-indole (4). 2,2',5,5,-Tetrabromo-3,3,-bi-l//-indole (1).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the chemical shift difference A6 between geminal axial and equatorial protons P to oxygen is -0.074ppm in tetrahydropyran (11) and about -0.80ppm in 1,3-dioxan (12). Our results seem to show that the same trend exists in seven-membered rings.…”
Section: Conformations Of the Seven-membered Ringsmentioning
confidence: 99%